Conductors' views on individual practice activities - Jossberger, Helen; Huovinen, Erkki; Ritter, Martin; Gruber, Hans (SAGE PUBLICATIONS INC, 2025)
This study explored how professional conductors understand the role of individual (purposeful) practice and how they describe the contents of such practice. Twelve professional conductors were interviewed and content analysis was used to analyze the data. The results show that the participants understood conducting as a lifelong learning process. Through intensive individual practice, they had built up a significant repertoire of musical works. Being well prepared allowed them to impart knowledge, which helped them to achieve an authoritative and communicative relationship with musicians. While technical aspects such as baton technique had been important during early career stages, these were mostly no longer practiced. Studying the score was perceived as the most central practice activity aiming at performance improvement. It required disciplined, persistent, and goal-oriented learning, and thus carried the marks of purposeful practice. Individual activities during score study were mainly carried out mentally and in particular situations supported with external tools (e.g., piano, audio recordings). The findings shed light on differences in opinion and implicit tensions, especially regarding memorization and the use of tools.